Neuerwerbungen : 1978. - Städtisches Kunstmuseum Bonn (Bonn : Städtisches Kunstmuseum Bonn, 1979)
Macke, August ; Campendonk, Heinrich ; Engert, Ernst Moritz ; Feldmann, Otto ; Henseler, Franz Seraph ; Macke, Helmuth ; Seehaus, Paul Adolf ; Thuar, Hans ; etc.
Neuerwerbungen : 1978, Städtisches Kunstmuseum Bonn, 5. - 28.10.1979
boek